Histology and cell biology : an introduction to pathology - Kierszenbaum, Abraham L.; Tres, Laura L. (Elsevier Saunders, 2012)
Histology and Cell Biology: An Introduction to Pathology uses a wealth of vivid, full-color images to help you master histology and cell biology. Dr. Abraham L. Kierszenbaum presents an integrated approach that correlates normal histology with cellular and molecular biology, pathology, and clinical medicine throughout the text. A unique pictorial approach-through illustrative diagrams, photomicrographs, and pathology photographs-paired with bolded words, key clinical terms in red, and clinical boxes and "Essential Concepts" boxes that summarize important facts give you everything you need to prepare for your course exams as well as the USMLE Step 1. Access the fully searchable text online at studentconsult.com, along with USMLE-style multiple-choice review questions, downloadable images, and online only references. Easily find and cross-reference information through a detailed table of contents that highlights clinical examples in red. Review material quickly using pedagogical features, such as Essential Concept boxes, bolded words, and key clinical terms marked in red, that emphasize key details and reinforce your learning. Integrate cell biology and histology with pathology thanks to vivid descriptive illustrations that compare micrographs with diagrams and pathological images